OPTIMISASI BIAYA BASIS DATA KOMPUTANSI AWAN RDS AWS - Budi Haryanto (Journal Of Communication Education, 2021)
The use of cloud technology is now starting to make some companies to moving database infrastructure to the cloud server, AWS (Amazon Web Service) as the number one cloud server provider provides many advantages when providing services, especially in database cloud computing.However, the many benefits provided by database cloud computing do not necessarily make companies immediately switch to cloud databases, even many who have tried cloud databases to return to onpremise systems, a constraint that is often found is the high costs incurred.Actually there are ways and techniques to minimize costs incurred while still getting optimal benefits. This writing discusses several things about how to optimize costs in database cloud computing.Keywords: Database, Cloud Computing, RDS, AWS, Cost Optimization